Hotel Choice Determinants in the North Rift Region of Kenya - B. Bor , Thomas (African Journal of Education,Science and Technology (AJEST), 2018)
Hotels form an important component and are critical to tourists’ destination choice and satisfaction. It is therefore imperative to understand the determinants of tourists’ choice of hotels especially for relatively ‘new’ destinations such as the North Rift region in Kenya. Literature suggests that tourists’ choices are complex and are driven by needs and judgments on the merits of the options available. This paper aims at establishing determinants considered important by tourists in their choice of hotels. The study was undertaken in six hotels located in three purposively selected counties namely, Uasin Gishu, Elgeyo Marakwet and Baringo in the North Rift region of Kenya. The study adopted descriptive research design wherein the sample comprised 240 tourists both domestic and international. However, only 191 (79.6%) managed to fill the questionnaires. Primary data was collected using structured questionnaires administered to tourists. Cronbachs’ Alpha was used to test the reliability of the research instrument. Descriptive statistics specifically mean and standard deviation were used to analyze data. Factor analysis was used to reduce the indicators to measurable variables. Descriptive results reveal that product range, value for money, location and staff related issues were crucial in determining hotel choice by tourists. On the other hand, factor analysis results grouped the 27 indicators into seven components that include facility elements, staff attributes, perceived value, quality aspects, accessibility, services offered and physical features as important indicators of hotel choice determinants. Based on the findings, the study concludes that tourists decisions are driven by attributes that require careful consideration that are crucial in creating visibility of an establishment. Thus the study recommends special attention towards ensuring that these factors are carefully observed in order to strategically place hotels within North Rift Region as a destination of choice for tourists. The findings can be used by the ministry of tourism when marketing North rift as a destination.